A meta-analytic examination of the potential correlates and consequences of workload - Bowling, Nathan A.; Alarcon, Gene M.; Bragg, Caleb B.; Hartman, Michael J. (Work and stress, 2015)
Over the last four decades, occupational stress researchers have given considerable attention to the potential correlates and consequences of workload. In the current study, we use meta-analysis (overall k = 336) to quantitatively review the workload literature. In analyses of hypothesized correlates, we found that social support was negatively associated (ρ = −.20 for supervisor support; ρ = -.11 for co-worker support) and that trait negative affectivity (ρ = .22), role ambiguity (ρ = .28), role conflict (ρ = .44) and work-family conflict (ρ = .44 for work-to-family conflict; ρ = .20 for family-to-work conflict) were each positively associated with workload. Analyses examining hypothesized outcome variables suggest that workload is negatively associated with several indices of psychological and physical well-being (ρs were generally in the -.20s and -.30s), and affective organizational commitment (ρ = -.11), and is positively associated with turnover intention (ρ = .16) and absenteeism (ρ = .07).